Sex and Time-of-Day Impact on Anxiety and Passive Avoidance Memory Strategies in Mice - Meseguer Henarejos, Ana Belén; Popović, Natalija; Bokonjić, Dubravko; Morales-Delgado, Nicanor; Alonso, Antonia; Caballero Bleda, María; Popović, Miroljub (Frontiers in Behavioral Neuroscience, 2020)
In humans, anxiety and cognitive processes are age, gender and daytime dependent. The purpose of the present study was to assess whether the daytime and sex influence on anxiety and emotional memory in adult mice. Light-dark and passive avoidance tests were performed at the beginning and at the end of the light cycle, defined as Zeitgeber time (ZT) ZT0-2.5 and ZT9.5-12, respectively. Baseline difference in anxiety was not found, but on the 24h retention trial of the passive avoidance test, females presented longer latencies to enter into the dark compartment at the ZT0-2.5 time point of the day. The data from the second test day (passive avoidance reversal trial) indicated that some animals associated the dark compartment with an aversive stimulus (shock), while others associated the aversive stimulus with crossing from one to another compartment. At the ZT9.5-12, female mice mainly related the aversive stimulus to transferring from one to another compartment, while male mice associated darkness with the aversive stimulus. There was a negative correlation between the frequency of light-dark transitions in the light-dark test and the passive avoidance latency on the 24h retention trial, in males tested at ZT0-2.5. The passive avoidance latency on the reversal and 24 h retention trials, negatively correlated with a risk assessment behaviour, in male mice tested on ZT0-2.5 and ZT9.5-12, respectively. In conclusion, our data reveal that the impact of motor activity and risk assessment behaviour, on passive avoidance memory formation and applied behavioural strategies, are time of day and sex dependent.